Studi Teoritis: Strategi Promosi Pelayanan Kesehatan Rumah Sakit Swasta Di Era Jaminan Pelayanan Kesehatan (JKN) - Wijaya Johanes Chendra; Dety Mulyanti (Lembaga Pengembangan Kinerja Dosen, 2023)
Facing the JKN era is not easy, especially for private hospitals. Private hospitals need strategy, understanding, understanding and mutual agreement throughout the internal hospital, both doctors, nursing staff, general staff and management. The strategy for promoting health services in hospitals and other health facilities is not much different from the marketing strategy in general. It aims to promote and introduce the Hospital and the services provided. The purpose of writing this scientific article is to find out and review from a theoretical point of view how the strategy is carried out by private hospitals in this JKN era. The method used is a theoretical study by analyzing and comparing existing theories. It then learns more about a subject in theory or research and helps readers understand it better and with implications. The results of this theoretical study are private hospital services by implementing strategies and principles for implementing the National Health Insurance Program (JKN) such as mutual cooperation, non-profit, openness, portability, membership, trust funds, and management. It can be concluded that the strategy for promoting health services in private hospitals is to implement them in accordance with established standards and laws. The health service quality strategy is also the main key to service promotion to increase patient satisfaction in receiving care. It is expected that hospital institutions will continue to provide excellent and comprehensive health services and meet the basic health needs of patients.